Advisory Committee on Administrative and Budgetary Questions - United Nations Department for General Assembly; Conference Management (United Nations, 2023)
This is the annual report submitted to the General Assembly by the Advisory Committee on Administrative and Budgetary Questions on the proposed programme budget for the year 2023.